LyGDI is a Promising Biomarker for Ovarian Cancer. Issue 3 (1st April 2010) - Zhen, Hongying; Yang, Shaomin; Wu, Hounan; Wang, Shuling; Lv, Jingqiao; Ma, Lijun; Zhang, Xiaowei
Abstract : Introduction: LyGDI is an inhibitor of Rho protein activation by blocking its transformation between guanosine 5′-diphosphate- and guanosine 5′-triphosphate-bound states. The aim of this study was to investigate the usefulness of LyGDI as a biomarker for the detection of ovarian cancer, and its specificity and sensitivity were compared with those of cancer antigen 125 (CA125). Methods: The serum levels of LyGDI were determined by enzyme-linked immunosorbent assay in 42 patients with ovarian disease, including 30 ovarian cancers and 12 benign ovarian lesions, and 76 healthy controls. The expression of LyGDI was also evaluated by immunohistochemical staining in resected ovarian tissues of these patients. Results: The serum LyGDI level of cancers was significantly greater than those of the benign and healthy groups ( P = 0.002 and P < 0.0001, respectively), whereas no difference was observed between the benign and control groups ( P = 0.889). Based upon receiver operating characteristic curve analysis, LyGDI levels were able to distinguish ovarian cancer from benign ovarian disease ( P = 0.0001) and healthy control ( P < 0.0001; areas under the receiver operating characteristic curves, 0.876 and 0.833, respectively). For ovarian cancers, 83.3% (25/30) or 80.0% (24/30) was identified by serum LyGDI (≥1.5 ng/mL) alone or by CA125 (>35 U/mL) alone. It is of particular importance to note that all cancer patients were identified by use of both markers, and the specificity was 83.3% for the benign group. Moreover, in early-stage cancers, 88.9% (8/9) had elevated serum LyGDI levels as compared with 44.4% (4/9) elevation of CA125 levels ( P = 0.125). Immunohistochemical staining confirmed the expression of LyGDI on cancerous epithelial cells other than benign ovarian epithelium. Conclusions: These results suggest that LyGDI has significant potential as a marker for detection of ovarian cancer in the patients with ovarian enlargement, including detection of early-stage cancers.